2011
DOI: 10.3354/dao02369
|View full text |Cite
|
Sign up to set email alerts
|

New records of Batrachochytrium dendrobatidis in Chilean frogs

Abstract: We used molecular techniques to examine 11 species of frogs in 6 localities in southern Chile to ascertain the incidence of the chytrid fungus Batrachochytrium dendrobatidis (Bd). We detected the fungus in 2 localities (Coñaripe and Raúl Marín Balmaceda) in 3 species: Batrachyla leptopus, Pleurodema thaul and Rhinoderma darwinii. Our findings expand the list of Bd hosts to include B. leptopus and P. thaul and extend the spatial distribution in Chile to include the southernmost Bd record at Raúl Marín Balmaceda. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…laevis, but expected to occur within the next years) all studied animals (eight) resulted positive for Bd. This pathogen has been reported from X. laevis in central Chile (Solís et al 2010) and from a range of native species across a latitudinal extension of ~3,000 km (Bourke et al 2011;Soto-Azat et al 2013a;Solís 2015). In the current study, we found the prevalence of Bd infection to range from zero to 41.7% in the X. laevis populations sampled, with all individuals showing low to moderate levels of infection, suggestive of a Bd reservoir function of this species when co-habiting with other susceptible amphibian species.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…laevis, but expected to occur within the next years) all studied animals (eight) resulted positive for Bd. This pathogen has been reported from X. laevis in central Chile (Solís et al 2010) and from a range of native species across a latitudinal extension of ~3,000 km (Bourke et al 2011;Soto-Azat et al 2013a;Solís 2015). In the current study, we found the prevalence of Bd infection to range from zero to 41.7% in the X. laevis populations sampled, with all individuals showing low to moderate levels of infection, suggestive of a Bd reservoir function of this species when co-habiting with other susceptible amphibian species.…”
Section: Discussionmentioning
confidence: 82%
“…Although poorly studied in South America, evidence of Ranavirus has been obtained from free-ranging amphibians in Venezuela, Argentina and Peru (Zupanovic et al 1998;Fox et al 2006;Warne et al 2016) and from farmed North American bullfrogs (Lithobates catesbeianus) from Uruguay and Brazil (Galli et al 2006;Mazzoni et al 2009). Better studied, Bd appears to be widely distributed in South America (Mazzoni et al 2003;Hanselmann et al 2004;Pounds et al 2006;Schloegel et al 2010Schloegel et al , 2012Solís et al 2010Solís et al , 2015Bourke et al 2011;Soto-Azat et al 2013a;Olson and Ronnenberg 2014;James et al 2015;Warne et al 2016).…”
Section: Introduction and Purposementioning
confidence: 99%
“…Infection with Bd has been reported in populations of the invasive African clawed frog, Xenopus laevis [24] in central Chile. Additionally, Bourke et al [25] , [26] recently described Bd infection in R. darwinii and two other native frog species in the south of the country. The impacts of this emerging disease on amphibian populations in Chile, including Darwin’s frogs, however, have not been studied.…”
Section: Introductionmentioning
confidence: 99%